Bioassay and Partial Identification of Non-Volatile Bioactive Compounds Produced By Bacillus Subtilis - Ithnin, Nalisha (2007)
Biological control of plant pathogens is an alternative to the strongly dependence of modern agriculture on chemical fungicides. Extensive applications of chemical control may lead to environmental pollution and development of resistant phytopathogenic fungi strains. It is therefore necessary to develop alternatives to synthetic chemical control to reduce the risks and raise consumer confidence. Bacillus subtilis (BS) was used in this study as the biological control agent (BCA) against Rhizoctonia solani (RS), Pythium ultimum (PU) and Sclerotium rolfsii (SR). The first part of this study focus on optimizing BS as BCA by examining application conditions using stability tests and bioassays. The effects of three variables namely temperature (-20oC-100oC), pH (3-11) and light (sunlight, UV and darkness) on the production of bioactive compounds were studied. From the dual culture bioassay, BS was found to suppress the growth of PU better than RS and SR. Temperature show a considerable effect on BS antifungal activity with highest inhibition occur on SR at 80oC (58.30%), followed by PU at -20oC treatment (38.68%) and RS at 30oC (35.39%). The optimal pH for antifungal production was pH 3 for RS (51.12%), pH 11 for SR (28.33%) and pH 7 for PU (28.73%). However, neither darkness nor UV treatment altered the antifungal activity. Darkness treatment managed to subdue PU (57.16%), RS (58.30%) and SR (46.24%). Thin layer chromatography (TLC) and high performance liquid chromatography (HPLC) were used in the second part of this study in order to screen and isolate the bioactive compound produced by BS. Methanolic extracts of BS was found to be the best extraction method from which 2 anticipated peaks with inhibitory activity against PU and Candida albicans (CA) were exhibited. However, the activity is more significant when tested against CA compared to PU due to concentration limitation. The TLC profiles of extracts revealed an identical chromatographic mobility to BS iturin A (Rf 0.51) and surfactin (Rf 0.68). Meanwhile through HPLC, homologous compound of fengycin and an iturinic compound were detected. The final part of this study was to determine the effectiveness of supplementing different carbon sources to BS on its antifungal activity and hydrolytic enzymes production. Bioassay was again applied to record the inhibitory activities. By using 1% (w/v) of three different carbon sources namely oil palm root (OPR), Ganoderma lucidum (GL) and ball-milled chitin (CHIT)], respectively, inhibitory activity of BS was induced compared to BS grown in Nutrient Agar (NA). Inhibitory activities (cm ± SD) for each pathogen were as followed: for PU, OPR (3.688 ± 0.01) > CHIT (2.304 ± 0.02) > GL (2.114 ± 0.1); for RS, CHIT (4.171 ± 0.05) > OPR (3.038 ± 0.66) > GL (2.892 ± 0.06); while for SR, OPR (2.927 ± 0.02) > CHIT (2.854 ± 0.06) > GL (2.843 ± 0.07). The exposure of selected phytopathogenic fungi to the hydrolytic enzymes such as chitinases, proteases or glucanases was found to degrade the structural matrix of fungal cell walls. BS was found to produce high chitinase in the medium containing CHIT (0.084 U/ml), followed by GL (0.056 U/ml) and OPR (0.051 U/ml), respectively. Meanwhile for β-1,3 and β-1,6-glucanase production, both OPR (1.099 U/ml, 0.716 U/ml) and GL (0.820 U/ml, 1.165 U/ml) showed higher production than CHIT (0.579 U/ml, 0.513 U/ml). The activity of protease was high when BS were cultured with GL (2.579 U/ml), followed by OPR (2.547 U/ml) and CHIT (2.548U/ml).